2016
DOI: 10.7717/peerj.2706
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA biogenesis pathway genes polymorphisms and cancer risk: a systematic review and meta-analysis

Abstract: MicroRNAs (miRNAs) may promote the development and progression of human cancers. Therefore, components of the miRNA biogenesis pathway may play critical roles in human cancer. Single nucleotide polymorphisms (SNPs) or mutations in genes involved in the miRNA biogenesis pathway may alter levels of gene expression, affecting disease susceptibility. Results of previous studies on genetic variants in the miRNA biogenesis pathway and cancer risk were inconsistent. Therefore, a meta-analysis is needed to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…Biogenesis of canonical microRNAs (miRNAs) involves multiple steps: nuclear processing of primary miRNA (pre-miRNA) by DROSHA, nuclear export of precursor miRNA (pre-miRNA) by Exportin 5 (XPO5), and cytoplasmic processing of pre-miRNA by DICER, however, DROSHA and DICER are essential for the miRNA maturation during the canonical miRNA pathway, but XPO5 can be complemented by alternative mechanisms [6]. In some pathological conditions, there has a dysregulation of this miRNA processing machinery components, such as the expression levels of Drosha and Dicer are down-regulated in ovarian cancer and neuroblastomas, while Exportin-5 is also down-regulated in bladder cancer [7]. When these matured miRNAs are processed and expressed, they bind to partially complementary sites in target mRNAs, leading to mRNA degradation or protein translation interference causing translational repression, mRNA destabilization, and/or mRNA cleavage for post-transcriptional regulation of protein synthesis [8,9].…”
Section: Mirnas: Treatment and Main Problemsmentioning
confidence: 99%
“…Biogenesis of canonical microRNAs (miRNAs) involves multiple steps: nuclear processing of primary miRNA (pre-miRNA) by DROSHA, nuclear export of precursor miRNA (pre-miRNA) by Exportin 5 (XPO5), and cytoplasmic processing of pre-miRNA by DICER, however, DROSHA and DICER are essential for the miRNA maturation during the canonical miRNA pathway, but XPO5 can be complemented by alternative mechanisms [6]. In some pathological conditions, there has a dysregulation of this miRNA processing machinery components, such as the expression levels of Drosha and Dicer are down-regulated in ovarian cancer and neuroblastomas, while Exportin-5 is also down-regulated in bladder cancer [7]. When these matured miRNAs are processed and expressed, they bind to partially complementary sites in target mRNAs, leading to mRNA degradation or protein translation interference causing translational repression, mRNA destabilization, and/or mRNA cleavage for post-transcriptional regulation of protein synthesis [8,9].…”
Section: Mirnas: Treatment and Main Problemsmentioning
confidence: 99%
“…microRNA (miR or miRNA) is an endogenous single-stranded small non-coding RNA, 18-25 nucleotides in length. miRNAs can bind to the 3'-untranslated region (UTR) of their target gene mRNAs to affect the stability of the mRNA, resulting in complete degradation or protein translation inhibition and negatively regulating gene expression at the post-transcriptional level (16). Numerous studies have demonstrated that the abnormal expression of miRNAs serves tumor-promoting or suppressing roles in the pathogenesis of malignant tumors and can affect tumor invasion and metastasis by regulating the expression of key genes (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of cell proliferation, transformation and tumorigenesis, miRNAs have been found to play essential roles . Specifically, more and more evidence has identified that abnormal miRNA expression is required for the initiation and procession of tumours . For melanoma, a battery of miRNAs has been found to be dysregulated .…”
mentioning
confidence: 99%